2018
DOI: 10.1016/j.neuron.2017.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Segmental Diversity of Spinal Inhibitory Interneurons

Abstract: Motor output varies along the rostro-caudal axis of the tetrapod spinal cord. At limb levels, ∼60 motor pools control the alternation of flexor and extensor muscles about each joint, whereas at thoracic levels as few as 10 motor pools supply muscle groups that support posture, inspiration, and expiration. Whether such differences in motor neuron identity and muscle number are associated with segmental distinctions in interneuron diversity has not been resolved. We show that select combinations of nineteen tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 57 publications
8
89
0
Order By: Relevance
“…In contrast, we observed a marked loss of cerebellar-projecting neurons from CC, and an expansion of Hoxc6-positive laminae V-VII SC neurons normally restricted to brachial levels, following the removal of a single Hox gene, Hoxc9 (Figures 3 and 5). Our data is broadly consistent with that observed for thoracic-level MNs (Dasen et al, 2003(Dasen et al, , 2005Jung et al, 2010) and spinal interneurons (Sweeney et al, 2018), whereby Hoxc9 alone is required to repress a brachial Hox code, thereby delineating axially-appropriate neural connectivity. An important point of difference of our work to this well-defined model, is that the marked loss of cerebellar-projecting CC neurons in Hoxc9 -/animals does not appear to be solely accounted for by a fate switch to a more rostral SC population.…”
Section: Hox Function Is Required To Axially Restrict Sc Populationssupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, we observed a marked loss of cerebellar-projecting neurons from CC, and an expansion of Hoxc6-positive laminae V-VII SC neurons normally restricted to brachial levels, following the removal of a single Hox gene, Hoxc9 (Figures 3 and 5). Our data is broadly consistent with that observed for thoracic-level MNs (Dasen et al, 2003(Dasen et al, , 2005Jung et al, 2010) and spinal interneurons (Sweeney et al, 2018), whereby Hoxc9 alone is required to repress a brachial Hox code, thereby delineating axially-appropriate neural connectivity. An important point of difference of our work to this well-defined model, is that the marked loss of cerebellar-projecting CC neurons in Hoxc9 -/animals does not appear to be solely accounted for by a fate switch to a more rostral SC population.…”
Section: Hox Function Is Required To Axially Restrict Sc Populationssupporting
confidence: 88%
“…This suggests potential expansion of a currently ill-defined brachial level SC population, which we predict would express a brachial Hox5-8 code, into more caudal levels. Hoxc9 is known to delineate the posterior boundary of brachial Hox expression and cell identity within ventral MNs and interneurons (Dasen et al, 2003(Dasen et al, , 2005Sweeney et al, 2018), though the cell-type exclusivity of this regulation is currently not known. Analysis of Hoxa5 and Hoxa6 expression in E15.5 ( Figure 5A) and E18.5 neural tube ( Figure S9A) shows widespread de-repression of these genes across much of the Hoxc9 -/thoracic spinal cord when compared to WT, suggesting multiple motor and sensory neural networks are likely to be coordinately mis- Figure 4A).…”
Section: Hoxc9 Regulates Region-specific Identity Of Sc Neuronsmentioning
confidence: 99%
“…Temporal stratification of neuronal subtypes by shared sets of TFs is probably only one of many mechanisms to generate neuronal diversity in the spinal cord. Recent work suggests the existence of scores of V1 neuron subtypes , Sweeney et al 2018. This number appears too high for conventional long-range developmental mechanisms.…”
Section: Temporal Specification Of Neuronal Subtype Identitymentioning
confidence: 95%
“…We found that SCTN subtypes can be defined by Recent studies suggest that molecular programs acting along the rostrocaudal axis play key roles in establishing subtype-specific features of spinal interneuron classes. Both V1 and V2a interneuron classes are generated from a single progenitor domain, but give rise to dozens of molecularly distinct subtypes, which can be defined through differences in settling position, connectivity, and transcription factor gene expression 21,22,31,32 . While studies of V1 interneurons have demonstrated an important role of Hox genes in patterning transcription factor expression 21 , the identities of their subtype-specific targets are unclear.…”
Section: Role Of Hox Genes In Determining Sctn Organization and Subtymentioning
confidence: 99%
“…Hox genes are expressed by multiple neuronal populations within the hindbrain and spinal cord, suggesting a broader role neuronal specification. Although recent studies have implicated Hox function during the differentiation of interneurons in the ventral spinal cord 21,22 , the identity of their downstream target effectors and potential roles in sensorymotor circuit assembly have not been investigated.…”
Section: Introductionmentioning
confidence: 99%